Rhinosporidiosis: Intraoperative Cytological Diagnosis in an Unsuspected Lesion. (11th October 2012) - Bhargava, Shruti; Grover, Mohnish; Maheshwari, Veena
Abstract : Rhinosporidiosis is a disease endemic to South India, Sri Lanka and some areas of the African continent. The nasal lesions can sometimes be confused with nasopharyngeal malignancy. We report here a clinically unsuspected case of rhinosporidiosis, diagnosed correctly by intraoperative FNAC, and later confirmed by histopathological examination.